Penerapan Metode Forward Chaining dan Naïve Bayes Untuk Mendiagnosa Penyakit Tanaman Kakao - Hilman Hadi; Ucuk Darusalam; Andrianingsih Andrianingsih (STMIK Budi Darma, 2021)
Cocoa is one of the many plantation products in Indonesia which has considerable economic value, and has plantation land and its production each year has increased significantly. The lack of agricultural extension experts in providing direction, guidance, and information dissemination about the development of cocoa plant diseases faced by the cultivators of these plants can have an impact on the cultivators. The method used in this research is the forward chaining and naïve Bayes method. This system is expected to be useful for users in diagnosing cocoa diseases independently, of course easily and efficiently without having to require experts in their fields, with reference to the results and discussions carried out, the accuracy of this system has an accuracy value of about 95% in carrying out the diagnosis